Woven terry fabrics : manufacturing and quality management - Singh, Jiten Pratap; Verma, Swadesh (Woodhead Publishing is an imprint of Elsevier, 2017)
"Woven Terry Fabrics: Manufacturing and Quality Management encompasses all aspects of terry fabric production, from raw material choice and weave design to technological developments, dyeing, and quality evaluation. Nothing feels more luxurious and comforting than wrapping myself or one of my children in a thick, soft, fluffy towel after bathing says Lindsey, a healthcare administrator and mother of two children in Boston. Consumers pay an average 15 USD for a bath towel. So, it has become a luxury item today. To meet the demand of growing population, the terry fabric industry has grown to a large extent. Lots of technological developments have taken place in this field."--Publisher's website
Includes index.
Keywords: Terry fabrics.; elektronické knihy; electronic books